Penerapaan Pendekatan Saintifik untuk Meningkatkan Kemampuan Pemahaman Matematika Ditinjau dari Gaya Belajar Siswa pada Materi Matriks - Virga Inesrawanti (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study aims to examine the extent to which students' abilities are in understanding mathematical concepts in depth, connecting them, and applying them in various life contexts. Improving mathematical understanding is considered to have a significant influence on the world of education. This is reflected in three main aspects: improving learning outcomes, strengthening critical thinking skills, and readiness to face global challenges in the 21st century. Students' learning styles are one of the important factors that influence mathematical understanding. Learning styles can be divided into three, namely visual (relying on sight), auditory (through hearing), and kinesthetic (through physical activity). Each individual generally has all three styles, but one of them will be more dominant. Students' ability to recognize and adjust their learning styles with appropriate learning strategies contributes to their success in understanding the material. This study uses a quantitative approach with a correlational survey technique. The research sample consisted of 30 grade XI students of SMK Ristek Jaya Jakarta. Data analysis was carried out through several stages, including the validity and reliability of learning style instruments and descriptive and inferential statistical tests such as regression and normality. The results of the analysis showed that the scientific approach had a significant influence on students' mathematical understanding, with a determination coefficient of 70.39%. This means that this approach contributes greatly to improving mathematical understanding based on students' learning styles. This study suggests further studies to deepen understanding of this phenomenon and make it a reference in learning practices.